2010
DOI: 10.3917/eg.392.0097
|View full text |Cite
|
Sign up to set email alerts
|

Lois d'échelle et transitions fractal-non fractal en géographie

Abstract: Résumé. Le concept de transition fractal -non fractal fut introduit initialement dans un cadre de physique fondamentale. Il est fondé sur le constat que le monde est globalement organisé de manière scalaire (comme fonction de l'échelle). Cette transition décrit le passage d'états non fractals (indépendants de l'échelle) à des états fractals (explicitement dépendants de l'échelle) et se manifeste localement sur des gammes d'échelles assez courtes. Ce concept permet de comprendre comment certains systèmes peuven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…In this case the fractal dimension is no longer constant, but varies in a linear way in terms of the logarithm of resolution. Many manifestations of such a behavior have been identified in human and physical geography [ 19 , 20 ]. law of “scale dynamics” involving a scale harmonic oscillator: For ε ≪ λ 0 it gives the standard scale invariant case = 0 (λ 0 / ε ) τ 0 , i.e.…”
Section: Brief Reminder Of the Theorymentioning
confidence: 99%
“…In this case the fractal dimension is no longer constant, but varies in a linear way in terms of the logarithm of resolution. Many manifestations of such a behavior have been identified in human and physical geography [ 19 , 20 ]. law of “scale dynamics” involving a scale harmonic oscillator: For ε ≪ λ 0 it gives the standard scale invariant case = 0 (λ 0 / ε ) τ 0 , i.e.…”
Section: Brief Reminder Of the Theorymentioning
confidence: 99%
“…Sur toutes ces innovations, parfois délaissées, se greffent de nouveaux développements : des modèles conceptuels graphiques sont approfondis par la théorie des graphes, et les systèmes dynamiques spatiaux bénéficient des avancées dans le calcul des équations différentielles partielles. Les jeunes DUPONT et les moins jeunes continuent d'innover, notamment en modélisant et en approfondissant les théories des systèmes complexes multi-échelles avec les approches fractales [Forriez & Martin, 2010, Dauphiné, 2011. Ils bénéficient des nombreux travaux effectués dans les disciplines voisines.…”
Section: Resultsunclassified
“…The application of the various tools and methods of the scale relativity theory to history and geography has been proposed by Martin and Forriez [34,61,35,36]. Forriez has shown that the chronology of some historical events (various steps of evolution of a given site) recovered from archeological and historical studies can be fitted by a log-periodic deceleration law with again g ≈ 1.7 and a retroprediction of the foundation date of the site from the critical date [34,35].…”
Section: History and Geographymentioning
confidence: 99%
“…Forriez has shown that the chronology of some historical events (various steps of evolution of a given site) recovered from archeological and historical studies can be fitted by a log-periodic deceleration law with again g ≈ 1.7 and a retroprediction of the foundation date of the site from the critical date [34,35]. Moreover, the various differential equation tools developed in the scale relativity approach both in scale and position space, including the nonlinear cases of variable fractal dimensions, have been found to be particularly well adapted to the solution of geographical problems [61].…”
Section: History and Geographymentioning
confidence: 99%
See 1 more Smart Citation